2012
DOI: 10.1017/s0029665112000456
|View full text |Cite
|
Sign up to set email alerts
|

A 12 week activity point system achieves weight loss in sedentary overweight and obese women: a pilot study

Abstract: The recent Scottish Health Survey reported that 65.1 % of adults in Scotland were overweight or obese (1) . It is well established that the low levels of activity are associated with increased body weight (2) and the current guidelines for activity are not being met with only 33 % of woman meeting the target of 30 minutes of activity most days of the week (1) . The aim of this study was to increase activity levels using a simple, self-guided activity point system (3) and assess changes in body weight. Overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…An intervention program focusing on activity can increase weight loss and decrease BMI. Findlay, Davison, Smith, and Jones reported that a 12-week intervention program focusing on increasing activity produced a significant decrease in weight and BMI [14]. The program sample included adult women with a BMI greater than 25 kg/m 2 .…”
Section: Length Of Programmentioning
confidence: 99%
See 1 more Smart Citation
“…An intervention program focusing on activity can increase weight loss and decrease BMI. Findlay, Davison, Smith, and Jones reported that a 12-week intervention program focusing on increasing activity produced a significant decrease in weight and BMI [14]. The program sample included adult women with a BMI greater than 25 kg/m 2 .…”
Section: Length Of Programmentioning
confidence: 99%
“…Participants were surveyed and height and weight were calculated at baseline, six weeks, and 12 weeks. However, only baseline and 12-week calculations were compared [14].…”
Section: Length Of Programmentioning
confidence: 99%
“…It is well established that the low levels of activity are associated with increased body weight (2) and the current guidelines for activity are not being met with only 33 % of woman meeting the target of 30 minutes of activity most days of the week (1) . The aim of this study was to increase activity levels using a simple, self-guided activity point system (3) and assess changes in body weight. Overweight and obese women (BMI > 25 kg/m 2 ) were recruited from the University.…”
mentioning
confidence: 99%